Enhancing Simulation Learning Through Collaborative Debriefing Papers - Martinez, Kelly (Nurse Educator, 2026)
Keywords: dept.nur

Redesigning ecosystems for all children to enhance health and well-being: An American Academy of Nursing consensus paper - Maughan, Erin D.; Meiers, Sonja J.; Breitenstein, Susan M.; Coffey, Jean S.; Cowen, Kay J.; Danford, Cynthia A.; Dodd, Catherine; King, Simmy; O'Malley, Donna M.; Resha, Cheryl-Ann; Sullivan, Mary C.; Lee, Susan K. (Nursing Outlook, 2026)
Although there have been many changes to community and family structure, and advances in scientific understanding of children's health and wellbeing, there has been little difference in how healthcare is delivered to children. The focus is often a deficit approach to acute situations. Halfon's Life Course Health Development Theory (LCHDT) focuses on a holistic approach to health and well-being. In the LCHDT, one's health is impacted by specific contexts during childhood that have a lasting impact. Key areas of family, community, schools, environment, and healthcare systems impart positive and negative experiences that affect children's health. Using the LCHDT as a guide, this consensus paper explores these five areas in the context of nursing practice roles and policy implications. With this approach, nurses lead and partner to build positive ecosystems for children and inform key policy actions to ensure change is a reality. © 2026 Elsevier Inc.
Keywords: Adolescents; Children; Ecosystems; Healthcare policy; Nursing care; dept.nur

Making arterial blood gas compensation memorable using a “buddy system” analogy - Diaz-Herring, Rosa (Nurse Educator, 2026)
Keywords: Analogy; Arterial blood; Blood gas analysis; Blood pressure; Compensation (psychology); dept.nur

Transforming clinical faculty preparation: A multistudent, multipatient simulation for nurse educator students - Kulacz, Regina; Lamberti, Amanda; Forte, Pamela; Lacey, Kimberly (Clinical Simulation in Nursing, 2026)
Keywords: Clinical Practice; Clinical faculty; Clinical judgment; Faculty development; Graduate students; Multipatient; Multistudent; Nurse education; Nurse educator; Nursing; Postgraduate; Role transition; Simulation; Student nurse; dept.nur

Restorative Masculine Integration Theory - Angelucci, Todd; Gallegos, Julian (American Journal of Men s Health, 2025)
The Restorative Masculine Integration Theory (RMIT) introduces a strengths-based, systems-oriented framework for promoting healthy masculinity through healing, leadership, and relational engagement. Developed in response to the adverse effects of masculine suppression, such as emotional disengagement, burnout, and polarity collapse, RMIT outlines a five-phase Cycle of Masculine Restoration: reclaimed masculinity, emotional safety and trust, grounded leadership, rebalanced gender polarity, and healing with cultural renewal. These stages are underpinned by core concepts including psychological safety, peer mentorship, emotional literacy, and authentic masculinity. Drawing from interdisciplinary foundations in gender studies, emotional intelligence, trauma-informed practice, polarity theory, and servant leadership, RMIT offers an adaptable framework for use across clinical, educational, organizational, and policy settings. Its alignment with the MANifest Health Theory further strengthens its applicability in men's health promotion. This manuscript elaborates the theory's conceptual development, visual model, and practical implications, while identifying future directions for empirical validation and inclusive application. RMIT advances a timely and restorative model for transforming masculine identity into a source of individual and collective resilience.
Keywords: Conceptual framework; Conceptual model; Culture theory; Empirical research; Gender identity; Grounded theory; Identity (music); Masculinity; PsycINFO; dept.nur; emotional literacy; masculinity; men’s health; peer mentorship; polarity; psychological safety; theory development; trauma-informed care

Virtual Faculty Development Program for Doctoral Advising - Penny, Frances (Nurse Educator, 2025)
Keywords: Academic advising; Career development; Faculty development; MEDLINE; Professional development; Virtual patient; dept.nur

Factors Contributing to Increased Mental Health Symptoms and Suicidality Among Sexual and Gender Minority Youth: A Scoping Review of Quantitative Research - Lopes, Daniela (Journal of Psychosocial Nursing and Mental Health Services, 2025)
Keywords: Anxiety; Clinical psychology; Depression (economics); Medicine; Mental health; Poison control; Psychiatry; Psychological intervention; Psychology; Psychosocial; Sexual minority; Sexual orientation; Suicidal ideation; Suicide prevention; dept.nur

Generational Differences in Nursing Students' Perceptions of Faculty Caring Behaviors and Presence in Online Registered Nurse to Bachelor of Science in Nursing Programs. - Macario, Kimberly Cardaci (International Journal for Human Caring, 2025)
Abstract: The purpose of this study was to explore how students of different generations perceived presence and caring behaviors by faculty in online Registered Nurse to Bachelor of Science in Nursing programs. Results showed that millennials reported statistically significant higher perceptions of social presence when compared with nonmillennials. Although generation was not a predictor of caring, all presence subscales were positively and significantly correlated with the total caring score. Teaching presence was a significant predictor of students' perceptions of caring in online courses.
Place: New York, New York
Keywords: Adult; Adult: 19-44 years; Age Factors; Caring Evaluation; Colleges and Universities; Conceptual Framework; Convenience Sample; Correlational Studies; Descriptive Research; Descriptive Statistics; Education; Non-Traditional; Education; Nursing; Baccalaureate; Educational Measurement; Exploratory Research; Faculty; Nursing; Faculty-Student Relations; Human; Intergenerational Relations; Learning Environment; Middle Age; Middle Aged: 45-64 years; Nursing Practice; Evidence-Based; Presence; Professional-Patient Relations; Program Evaluation; Quantitative Studies; Questionnaires; Registered Nurses Psychosocial Factors; Regression; Social Behavior Evaluation; Statistical Significance; Student Attitudes Evaluation; Students; Nursing Psychosocial Factors; Summated Rating Scaling; Teaching Methods; United States; dept.nur

Summer Nursing Symposium: An Immersive Educational Program Inspiring Underrepresented Minorities for College and a Career in Nursing - Knickerbocker, Joshua; Krol, Maria; Bartlett, Andrew; Borgognone, Kristen; Martinez, Kelly (Hispanic Health Care International, 2025)
Keywords: Medical education; Medicine; Nurse education; Nursing; Psychology; Underrepresented Minority; dept.nur; peer-reviewed

Become a journal reviewer: a vital component of lifelong learning - Resha, Cheryl (The Journal of School Nursing, 2024)
Keywords: dept.nur

Collaborating to prepare students for perioperative nursing - Lacey, Kimberly; Forte, Pamela; Tammaro, Marie (Nurse Educator, 2024)
An abstract is unavailable.
Keywords: dept.nur; peer-reviewed

Use of student-created simulations to assess competency - Prendergast, Krista M.; Morrill, Deborah (Nurse Educator, 2024)
An abstract is unavailable.
Keywords: dept.nur; peer-reviewed

Use of an Affective Teaching Intervention to Impact Connections Between Academic and Professional Integrity - Morrill, Deborah (Southern Connecticut State University, 2021)
Dishonesty and misconduct of nursing students during their education is a continuing concern, especially as it relates to expected professional behaviors. This quasi experimental pre-and post-interventional study explored the impact of an affective learning module on developing beliefs and perceptions of ethicality of academic and professional misconduct of students in a BSN program. A modified version of McCrink’s (2008) tool, entitled “Nursing Student Experiences and Perceptions of Academic and Professional Conduct Survey” measured these constructs. The affective learning module, based on Rest’s theory of moral development, and Krathwohl’s affective taxonomy, actively engaged students in ethical decision-making with connections to professional practice through discussion, case review and reflection. The pretest data (N=65) analysis using Mann Whitney U, indicated differences in mean rank related to enrollment status, healthcare work experience and gender and beliefs, and perceptions of academic and professional misconduct. A comparative analysis (N=16) of pre and posttest data was limited due to required changes related to the COVID-19 pandemic. Changes in pre and posttest data suggest the need to replicate and continue research in the area of intentional affective teaching of ethicality and professional values.
Keywords: Affective domain; Affective taxonomy; Dishonesty; Integrity; Misconduct; Value development; dept.nur

An Innovative Academic/Practice Partnership to Support Nursing Workforce Needs and Student Clinical Education - Hahn, Judith; Resha, Cheryl-Ann; Beauvais, Audrey; Beckman, Beth; Forte, Pamela; Rebeschi, Lisa M.; Snyder, Marianne (JONA: The Journal of Nursing Administration, 2023)
Innovation is needed to solve nursing workforce issues during times of crisis. A collaborative effort between a hospital system and several universities resulted in the Bridge to Professional Practice Program that was implemented during a period of high patient volume and nursing student downtime. The program provided support for staffing needs and clinical hours to promote readiness for practice for students. The program evaluation outcomes and recommendations for improvement are addressed.
Keywords: dept.nur; peer-reviewed

Preface - Logan, Isabel; Green, Cheryl (Stabilization Approaches That Empower Clients Through Mental Health Crises, 2023)
Keywords: dept.nur; dept.swk

Use of a supplemental feeding tube device and breastfeeding at 4 weeks - Penny, F.; Brownell, E.A.; Judge, M.; Marshall-Crim, M.; Cartagena, D.; McGrath, J.M. (MCN The American Journal of Maternal/Child Nursing, 2023)
Background:Mothers having difficulty breastfeeding their infants may use alternative supportive feeding methods. Although a supplemental feeding tube device is commonly used, efficacy for supporting sustained breastfeeding remains unknown.Purpose:To describe supplemental feeding tube device use by breastfeeding mothers as an alternative feeding method through exploration of associations between supplemental feeding tube device use and continued breastfeeding at 4 weeks of infant's age.Method:Forty mothers participated. They were interviewed during the birth hospitalization and at 4 weeks postpartum. Questions addressed use of supplemental feeding tube devices, breastfeeding issues, and continued breastfeeding relationships. We examined the relationship between LATCH scores at 2 to 3 days of life.Results:Breastfeeding mothers who chose to supplement with bottle-feeding instead of use of a supplemental feeding tube device were 30% less likely to continue breastfeeding at a medium/high/exclusive level.Conclusion:Use of the supplemental feeding tube device may help avoid the potentially detrimental effect of bottle-feeding on continued breastfeeding. © 2023 Lippincott Williams and Wilkins. All rights reserved.
Keywords: Baby-friendly hospital initiative; Bottle-feeding; Breast feeding; Breastfeeding exclusive; Exclusive breastfeeding; Human milk; Lactation; dept.nur; peer-reviewed

Unfolding health assessment case studies for the student nurse - Maynard, Kristi; Adimando, Andrea (Sigma Theta Tau International, 2020)
This book was designed with student nurses in mind. It is intended to serve as a tool to provide practice, enhance learning, and increase the propensity for retention and application of basic concepts of health and physical assessment. The book can be used by early-career nursing students who have just begun to cover its concepts as well as by pre-licensure exam students who may benefit from reiteration and reinforcement of concepts learned early on in nursing school and from practicing applying these concepts to more complex scenarios.Divided into 13 chapters, all of which are geared toward a particular subject matter. Chapters 1 and 2 introduce the concept of an unfolding case study and the nursing process. Chapter 3 provides an in-depth guide to answering NCLEX-style questions. There are several NCLEX-style questions broken down and analyzed within this chapter and several practice questions for your benefit. The remainder of the chapters are subject-based and cover assessment of the major body systems in a systematic and learner-friendly way. Readers will notice that while each chapter covers different content matter, the chapters are structured in similar ways so the reader can begin to develop a feel for and familiarity with an unfolding case study analysis.Goals for the book are:*Increased comfort level and confidence in analyzing patient scenarios in regards to basic health assessment *A more in-depth knowledge of basic health assessment concepts *Ample chances to practice applying concepts learned in your health assessment course to solidify the information you have learned*Increased confidence in answering NCLEX-style questions *Increased knowledge, skill levels, and confidence in assessing and managing patients with a variety of healthcare needsThe chapters of the book do not have to be completed in any particular order, as they are each individualized to certain subject matter categories. The authors recommend you use these unfolding case studies as a means of evaluating the ability to think critically and apply the concepts learned in health assessment classes to realistic patient scenarios. The book can be used as a study tool during health assessment classes, a health assessment refresher tool during other classes, and an NCLEX study tool after finishing nursing school.
Keywords: dept.nur

Stabilization approaches that empower clients through mental health crises - Logan, Isabel; Green, Cheryl A. (IGI Global, 2023)
Mental health practitioners often overlook initial stabilization strategies and interventions when providing evidence-informed approaches in order to get to the so-called “important” or “interesting” part of treatment. For many mental health practitioners, the “important” or “interesting” component...
Publication Title: https://services.igi-global.com/resolvedoi/resolve.aspx?doi=10.4018/978-1-7998-8228-2
Keywords: dept.nur; dept.swk

Grow through what you go through - Ortiz, Chelsea L. (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
Being a millennial person-of-color in the twenty-first century is exhaustive in itself—adding the vulnerabilities of a global pandemic magnified that undertaking. As women, we bear the responsibilities of balancing our professional life with our family life; our role as a partner or friend with our role as an individual being; and our mental health with our social health. “Grow Through What You Go Through” explores the value of saying “Yes, I can do this too” when COVID-19 gave many a reason to say, “I’ve had enough.” Between being a supportive partner and family member to many who experienced financial and educational setbacks and being an important part of preparing the next set of future nurses to lead and excel during a global pandemic, COVID-19 enlightened my perspective on who I was at the start of COVID-19 and the person I would turn out to be by the end of it.
Keywords: COVID-19; Coping; Resilience; dept.nur

Autonomic modulation, spontaneous baroreflex sensitivity and fatigue in young men after COVID-19 - Latchman, Peter L; Yang, Qin; Morgenthaler, Diane; Kong, Lingsong; Sebagisha, J.; Melendez, Luke; Green, Cheryl A.; Bernard, Stanley; Mugno, Raymond; De Meersman, Ronald (Physiological research, 2023)
Impaired autonomic modulation and baroreflex sensitivity (BRS) have been reported during and after COVID-19. Both impairments are associated with negative cardiovascular outcomes. If these impairments were to exist undetected in young men after COVID-19, they could lead to negative cardiovascular outcomes. Fatigue is associated with autonomic dysfunction during and after COVID-19. It is unclear if fatigue can be used as an indicator of impaired autonomic modulation and BRS after COVID-19. This study aims to compare parasympathetic modulation, sympathetic modulation, and BRS between young men who had COVID-19 versus controls and to determine if fatigue is associated with impaired autonomic modulation and BRS. Parasympathetic modulation as the high-frequency power of R-R intervals (lnHFR-R), sympathetic modulation as the low-frequency power of systolic blood pressure variability (LFSBP), and BRS as the -index were measured by power spectral density analysis. These variables were compared between 20 young men who had COVID-19 and 24 controls. Independent t-tests and Mann-Whitney U tests indicated no significant difference between the COVID-19 and the control group in: lnHFR-R, P=0.20; LFSBP, P=0.11, and -index, P=0.20. Fatigue was not associated with impaired autonomic modulation or BRS. There is no difference in autonomic modulations or BRS between young men who had COVID-19 compared to controls. Fatigue did not seem to be associated with impaired autonomic modulation or impaired BRS in young men after COVID-19. Findings suggest that young men might not be at increased cardiovascular risk from COVID-19-related dysautonomia and impaired BRS.
1 citations (Crossref) [2023-10-31]
Keywords: Autonomic Nervous System; Baroreflex; Blood Pressure; COVID-19; Cardiovascular System; Heart Rate; Humans; Male; dept.hms; dept.mat; dept.nur; dept.pch; dept.ss; peer-reviewed

Integration of the Registered Nurse Care Coordinator Role in a Federally Qualified Health Center - Alicea-Planas, Jessica; Burger, Susan (The Journal of Ambulatory Care Management, 2023)
The purpose of this 1-group, retrospective case study was to analyze the expanded role of registered nurse care coordination (RNCC) on health outcomes in a primary care setting in its real-life context. The convenience sample consisted of 244 adults diagnosed with uncontrolled diabetes mellitus and/or hypertension. Secondary data entered into the electronic health record by the health care team during patient visits pre- and post-implementation of the RNCC program were analyzed. Clinical findings suggest that RNCC may provide a valuable service. Additionally, financial analysis demonstrated that the cost of the RNCC position was both self-sustaining and revenue producing.
0 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

A telemedicine standardized patient experience: enhancing the virtual classroom and preparing for alternative modalities of care - Maynard, Kristi; Knickerbocker, Joshua (Nursing Education Perspectives, 2023)
This pilot study explored the use of standardized patients in the virtual classroom in efforts to increase family nurse practitioner preparedness to engage in telemedicine care delivery. Using a mixed-methods approach, we determined this innovation significantly increased students' confidence in their ability to perform a telemedicine visit while also improving their satisfaction with the virtual classroom.
1 citations (Crossref) [2023-10-31]
Keywords: Delivery of Health Care; Humans; Personal Satisfaction; Pilot Projects; Students; Telemedicine; dept.nur; peer-reviewed

Diabetes Distal Peripheral Neuropathy: Subtypes and Diagnostic and Screening Technologies - Newlin Lew, Kelley; Arnold, Tracey; Cantelmo, Catherine; Jacque, Francky; Posada-Quintero, Hugo; Luthra, Pooja; Chon, Ki H. (Journal of Diabetes Science and Technology, 2022)
Diabetes distal symmetrical peripheral neuropathy (DSPN) is the most prevalent form of neuropathy in industrialized countries, substantially increasing risk for morbidity and pre-mature mortality. DSPN may manifest with small-fiber disease, large-fiber disease, or a combination of both. This review summarizes: (1) DSPN subtypes (small- and large-fiber disease) with attention to clinical signs and patient symptoms; and (2) technological diagnosis and screening for large- and small-fiber disease with inclusion of a comprehensive literature review of published studies from 2015-present (N = 66). Review findings, informed by the most up-to-date research, advance critical understanding of DSPN large- and small-fiber screening technologies, including those designed for point-of-care use in primary care and endocrinology practices.
3 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

Moral distress in emergency and critical care nurses: A metaethnography - Arnold, Tracey C (Nursing Ethics, 2020)
Background:Moral distress has detrimental effects on nurses which impacts the entire healthcare cycle. Described as a crescendo effect, resolved situations of moral distress leave residue on the nurse with three potential outcomes: moral numbing, conscious objection to the situation, and burnout.Objective:This metaethnography strives to achieve a fuller understanding of moral distress by interpreting the body of qualitative work of moral distress in emergency and critical care nurses.Method:This study used the Noblit and Hare?s approach of interpretative synthesis. Ten studies met the criteria and were used in this synthesis.Ethical considerations:Ethical issues were minimal since no human subjects were involved. Ethical requirements were respected in all study phases.Results:The synthesis of qualitative research on moral distress resulted in one central theme, ?the battle within,? and five subthemes.Conclusions:The unique nature of this nursing specialty resulted in a lasting inner conflict for nurses that is consistent with the previously described crescendo effect. The effects are complex and long lasting and may potentially affect the nurses? future patient care.
17 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

An evolutionary concept analysis of secondary traumatic stress in nurses - Arnold, Tracey (Nursing Forum, 2020)
Purpose The purpose of this article is to provide conceptual clarification of secondary traumatic stress (STS) in nurses. Background As an empathetic helping profession, nurses are at increased risk for STS. Interchangeable usage of related terms among multidisciplinary literature has resulted in lack of conceptual clarity resulting in conflation of terms. Conceptual clarity is necessary for a foundation for further research on treatment. Methods Rodgers' evolutionary model of concept analysis. Results Nurses are predisposed to STS due to exposure, empathy, bonding, and personal factors. Essential attributes were found to be posttraumatic stress disorder-like symptoms, biological symptoms, social symptoms, and psychological symptoms. Resultant consequences included an altered worldview, interpersonal difficulties, and decreased occupational commitment. Conclusion This concept analysis, the first focusing on STS, provides conceptual clarity and a concept map of STS within the nursing population.
17 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/nuf.12409
Keywords: Rodgers' evolutionary model; concept analysis; concept map; dept.nur; peer-reviewed; secondary traumatic stress

Humanizing substance abuse: a theory-based educational intervention for undergraduate nursing students - Roncallo, Hannah R.; Aronson, Barbara (Journal of Addictions Nursing, 2023)
Background Healthcare providers, as well as healthcare students, have been found to harbor negative attitudes toward individuals with substance abuse disorders, impacting the care they give and subsequently creating poor patient outcomes. Purpose This study seeks to determine the effectiveness of an educational intervention, grounded in theory, toward changing nursing student attitudes regarding patients with a substance abuse disorder. Methods Nursing students participated in a teaching intervention, developed using the experiential learning theory, that utilizes modalities for each kind of learner aimed at reducing bias toward this population. The Medical Condition Regard Scale was used pre/post intervention to determine regard toward patients with the diagnosis of substance abuse. Results Student nurses maintained the least favorable attitudes toward individuals who abuse substances in comparison with patients with the diagnoses of pneumonia or gastroesophageal reflux disease; there were significant differences in attitudes toward patients who abused substances before and after participation in the educational intervention, with postparticipation attitudes being significantly more positive than attitudes before participation. Students found the educational intervention and debriefing highly satisfactory. Implications This educational intervention can provide a cost-effective, easy-to-replicate, time-efficient learning activity that could be added to undergraduate nursing curriculum.
0 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

Differences in Neonatal Outcomes Among Premature Infants Exposed to Mother's Own Milk Versus Donor Human Milk - Cartagena, Diana; Penny, Frances; McGrath, Jacqueline M.; Reyna, Barbara; Parker, Leslie A.; McInnis, Joleen (Advances in Neonatal Care: Official Journal of the National Association of Neonatal Nurses, 2022)
BACKGROUND: Growing evidence supports the superior benefits of exposure to mother's own milk (MOM) in reducing prematurity-related comorbidities. Neonatal exposure to donor human Milk (DHM) is a suitable alternative when MOM is insufficient or unavailable. However, the same protective composition and bioactivity in MOM are not present in DHM. Additional evidence is needed to justify and inform evidence-based practices increasing MOM provision while optimizing adequate use of DHM for premature infants. PURPOSE: A systematic review of the literature was conducted to determine differences in neonatal outcomes among premature infants exposed to predominately MOM versus DHM. METHODS/SEARCH STRATEGY: Databases including PubMed, CINAHL and Cochrane were searched (2020-2021) using the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analysis) guidelines. Evidence was classified using the John Hopkins evidence-based practice levels and quality of evidence. RESULTS: Eleven studies met inclusion criteria. Studied neonatal outcomes included ( a ) growth parameters (n = 8), ( b ) neonatal morbidities (n = 6), and ( c ) gut microbiome (n = 4). Overall, evidence suggests DHM exposure is beneficial but not equivalent to MOM feeding. Compared with DHM, greater doses of MOM are ideal to enhance protection primarily related to infant growth, as well as gut microbiome diversity and richness. IMPLICATIONS FOR PRACTICE: Standardized and evidence-based practices are needed to clearly delineate optimal use of DHM without undermining maternal and neonatal staff efforts to support and promote provision of MOM. IMPLICATIONS FOR RESEARCH: Additional evidence from high-quality studies should further examine differences in neonatal outcomes among infants exposed to predominately MOM or DHM in settings using standardized and evidence-based feeding practices.
2 citations (Crossref) [2023-10-31]
Keywords: Breast Feeding; Female; Humans; Infant; Infant; Newborn; Infant; Premature; Infant; Very Low Birth Weight; Intensive Care Units; Neonatal; Milk; Human; Mothers; dept.nur; peer-reviewed

Fostering Nursing Students' Moral Decision-Making Through Use of an Affective Learning Module - Morrill, Deborah; Westrick, Susan J. (Nurse Educator, 2022)
Background: The emphasis on disciplinary and preventive approaches to combating academic misconduct does little to foster student professional identity and core nursing value formation. Problem: There is a need for pedagogy designed to navigate moral decision-making within ambiguous areas of practice as nursing students integrate personal and professional values while becoming a nurse. Approach: Rest's theory of moral development offers a framework for constructing purposeful affective learning activities that operationalize moral sensitivity, judgment, motivation, and character, whereas Krathwohl's theory provides a means to identify affective learning objectives. Offering prelicensure nursing students an opportunity to discuss, reflect on, and consider actions and consequences associated with academic and practice-based situations forms the basis for this affective learning module that fosters connections between academic and professional behaviors of integrity. Conclusion: Rest's theoretical model provides a viable structured approach to moral development. Curriculum designed to engage moral decision-making offers an innovative approach to cultivating student integrity.
1 citations (Crossref) [2023-10-31]
Keywords: dept.nur; peer-reviewed

Beyond the Pain - Green, C. (Research Anthology on Nursing Education and Overcoming Challenges in the Workplace, 2021)
Healthy workplaces promote inclusionary behaviors. When nurses experience exclusionary behaviors such as bullying and incivility, there may also be hidden issues with acceptance of diversity in the workplace environment. Educating nursing staff on the importance of variations in age, culture, gender, sex, race, ethnicity, and religion in the workplace can help facilitate communication among staff. For example, organizations can use educational forums to discuss how different cultures vary in the addressing of conflict within the workplace; some cultures may prefer to reach consensus rather than be confrontational. Chapter 5 discusses strategies that nurses and organizations can implement, such as Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS). TeamSTEPPS is a curriculum that can be used to improve teamwork skills, communication, and build team collaboration. © 2021, IGI Global.
Pages: 402-417 tex.document_type: Book Chapter tex.source: Scopus
Keywords: dept.nur

And sometimes, we say good night - Green, C. (International Journal of Africa Nursing Sciences, 2022)
The evolution of life is that one day after we are born, we must say good night, and fall asleep and breath no more. The trepidation of death is more than the ceasing of lung, cardiac, and brain function; for the nurse who loses a nurse colleague, it is a farewell of a collegial relationship that developed in the process of healing others. The death of a nurse colleague is sacred. © 2022
0 citations (Crossref) [2023-10-31] tex.art_number: 100400 tex.author_keywords: Bereavement; End-of-life care; Grief; Nurse colleague; Sacred tex.document_type: Article tex.source: Scopus
Keywords: article; bereavement; brain function; breathing; dept.nur; grief; heart function; human; lung function; night; nurse; peer-reviewed; terminal care

Applying the nightingale pledge in reducing health disparities: A hospital-acquired pressure injury case study - Green, C. (Advances in skin & wound care, 2022)
ABSTRACT: Professional nurses, by virtue of their training, pledge to care for individuals who are sick or infirm. This commitment is confirmed via the Nightingale Pledge, which focuses on public health and equity and deems the nurse to be a missioner of health. Health disparities exist in direct conflict with the nursing responsibility of caritas, or love. Accordingly, it is imperative that nurse educators create learning environments that are conducive to comfortably discussing differences in physical assessments performed on diverse populations as part of their work to eliminate health disparities and in accordance with the Nightingale Pledge. Copyright © 2022 Wolters Kluwer Health, Inc. All rights reserved.
0 citations (Crossref) [2023-10-31] tex.document_type: Article tex.pubmed_id: 35188485 tex.source: Scopus
Keywords: Hospitals; Humans; dept.nur; hospital; human; peer-reviewed

The Effects of a Deliberate Practice Debriefing During a Response to Rescue Patient Simulation With Undergraduate Nursing Students - Aronson, Barbara; Bell, Arleigh; Andrighetti, Tia; Meyer, Mary; Shepherd, Karen; Bambini, Deborah (Nursing Education Perspectives, 2021)
The purpose of this multisite, randomized, pretest/posttest quasi-experimental study was to compare student nurse competency, learning retention, and perceived student support after exposure to a deliberate practice debriefing versus standardized debriefing. Fifty undergraduate students participated in the complex response to rescue simulation. The intervention group had significantly higher total mean and three subscale scores on the competency tool than the comparison group, although differences in learning retention and student support were not significant. This study provides preliminary support for the effectiveness of deliberate practice debriefing to enhance students’ mastery of skills and behaviors in complex simulations.
0 citations (Crossref) [2023-10-31]
Keywords: Baccalaureate; Clinical Competence; Education; Humans; Nurses; Nursing; Patient Simulation; Simulation Training; Students; clinical competence; dept.nur; human; nurse; nursing education; nursing student; patient simulation; peer-reviewed; simulation training

Cognitive behavioral therapy to sustain the antidepressant effects of ketamine in treatment-resistant depression: A randomized clinical trial. - Wilkinson, Samuel T.; Rhee, Taeho Greg; Joormann, Jutta; Webler, Ryan D.; Lopez, Mayra Ortiz; Kitay, Brandon M.; Fasula, Madonna K.; Elder, Christina; Fenton, Lisa R.; Sanacora, Gerard (Psychotherapy and Psychosomatics, 2021)
Introduction: Ketamine has emerged as a rapid-acting antidepressant. While ongoing treatment can prevent relapse, concerns exist regarding long-term exposure. Objective: We conducted a randomized trial to examine the feasibility and efficacy of cognitive behavioral therapy (CBT) following intravenous ketamine in treatment-resistant depression (TRD). Methods: Subjects with TRD were recruited and treated with 6 intravenous infusions of ketamine over 3 weeks. Subjects who experienced a clinical response (≥50% improvement in depression severity) were then randomized to receiving CBT or treatment as usual (TAU) for an additional 14 weeks, using a sequential treatment model. Results: Of the 42 patients who signed consent, 28 patients achieved a response and were randomized to CBT or TAU. When measured using the Montgomery-Asberg Depression Rating Scale (primary outcome measure), the effect size at the end of the study was moderate (Cohen d = 0.65; 95% CI -0.55 to 1.82), though the group-by-time interaction effect was not significant. There was a significant group-by-time interaction as measured by the Quick Inventory of Depressive Symptomatology (F = 4.58; p = 0.033), favoring a greater sustained improvement in the CBT group. This corresponded to a moderate-to-large effect size of the Cohen d = 0.71 (95% CI -0.30 to 1.70) at the end of the study (14 weeks following the last ketamine infusion). In a subset of patients (N = 20) who underwent cognitive testing using the emotional N-back assessments before and after ketamine, ketamine responders showed improvement in the accuracy of emotional N-back (t[8] = 2.33; p ¡ 0.05) whereas nonresponders did not (t[10] ¡1; p ns). Conclusions: This proof-of-concept study provides preliminary data indicating that CBT may sustain the antidepressant effects of ketamine in TRD. Further study and optimization of this treatment approach in well-powered clinical trials is recommended. © 2021 S. Karger AG, Basel. Copyright: All rights reserved.
36 citations (Crossref) [2023-10-31]
Keywords: Antidepressive Agents; Article; Cognitive Behavioral Therapy; Depression; Depressive Disorder; Humans; Ketamine; Major; Treatment Outcome; Treatment-Resistant; adult; antidepressant activity; antidepressant agent; clinical article; clinical effectiveness; clinical outcome; cognitive behavioral therapy; continuous infusion; controlled study; depression; dept.nur; female; human; ketamine; major depression; male; peer-reviewed; prophylaxis; prospective study; randomized controlled trial; relapse; treatment outcome; treatment resistant depression

Flu vaccinations: College campus not making the grade. A study of influenza vaccination at an urban public university. - Kreiger, Joan E; Zigmont, Victoria A.; Michalski, Carrie D; Borgognone, Kristen S (Journal of American college health : J of ACH, 2021)
Objective: Even healthy college students are vulnerable to severe complications associated with seasonal influenza (flu). Despite national directives to increase influenza vaccination compliance, college campuses remain woefully below national goals. This study aimed to identify factors correlated with the decision to voluntarily receive an influenza vaccine. Additionally, students’ reasons for non-vaccination were also examined. Participants: 1021 undergraduate students across four professional schools. Methods: A representative cross-sectional survey was conducted at a public, urban university. Results: The survey measured self-reported influenza vaccination: an overall influenza vaccination rate of 38% was identified. Student characteristics associated with increased influenza vaccination included students’ enrollment in academic health disciplines; being female; human papillomavirus (HPV) vaccination; and no marijuana use in the last month. Barriers to influenza vaccination included contraindications, mistrust issues, and personal reasons. Conclusion: Universities that can identify facilitators and barriers to voluntary influenza vaccination can assist with program initiatives to improve influenza vaccination compliance rates. © 2021 Taylor & Francis Group, LLC.
2 citations (Crossref) [2023-10-31] https://pubmed.ncbi.nlm.nih.gov/34670106/
Keywords: dept.hms; dept.nur; dept.pch; peer-reviewed

Examining and Solving Health Disparities in the United States: Emerging Research and Opportunities - Green, Cheryl (Medical Information Science Reference, 2021)
"This book provides awareness and discussion on the topic of inequities in healthcare that impact health disparities"–
Keywords: Health status indicators; United States; Health Status Disparities; Healthcare Disparities; United States; Health services accessibility; dept.nur; economics; Health Services Accessibility; economics; Socioeconomic Factors; Minority Health; United States; faculty_collection

The search for support and healing - Green, Cheryl (Research Anthology on Nursing Education and Overcoming Challenges in the Workplace, 2021)
Chapter 6 provides nurses, nurse leaders, and organizations interventions to understand, confront, and eliminate bullying and incivility from the workplace. Emotional intelligence (EI) and cognitive rehearsal are techniques when taught to nurses via in-services provided by organizations, can build awareness of verbal and nonverbal cues used in their communication as well as those of others. By understanding how we communicate and respond to others and vice versa, insight to what are appropriate and inappropriate responses can hold nurses accountable to how they treat one another. The neuroscience of oxytocin release at a biochemical level supports the benefits of organizations investing in the mental and physical health of their employees by empowering them to grow individually and as a collaborative team. © 2021, IGI Global.
Keywords: dept.nur

Complexity science, nursing, and COVID-19 - White, Kenneth R.; Begun, James W.; Vicenzi, Angela E (The American journal of nursing, 2021)
Understanding a bewildering crisis like a pandemic as 'normal' may be empowering. Copyright © 2021 Wolters Kluwer Health, Inc. All rights reserved.
0 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103432985
Keywords: COVID-19; Health Policy; Humans; Nurse's Role; Systems Analysis; dept.nur; epidemiology; health care policy; human; nurse attitude; peer-reviewed; system analysis; therapy

The hollow: A theory on workplace bullying in nursing practice - Green, C. (Nursing Forum, 2021)
Background: Incivility and bullying within the profession of nursing remains a problem within the workplace. As a result, healthcare workplaces can become unhealthy and difficult for nurses to function within. Work productivity is impacted and patients' healthcare is placed at risk when nurses are emotionally and physically affected by workplace incivility and bullying. Clinical nurse leaders (CNLs) applying theoretical reasoning and nursing competencies' in addressing bullying and incivility within the workplace, can provide an organized and effective organizational approach to addressing bullying and incivility in work environments. Methods: Theoretical reasoning and nursing competencies in addressing bullying and incivility within the workplace, will be examined as a means to identify nurses exhibiting signs and symptoms of bullying and incivility in work environments. The theory of The Hollow will identify the origins of affected nurses' behaviors and the physiological and psychological impact of bullying and incivility. The CNL role will be used as a facilitator of change at the microsystem level. And competencies for addressing behaviors associated with bullying and incivility will be addressed. Approach: Innovation adapted from prior research and literature developed by the author, extrapolated from the literature on workplace bullying and incivility in nursing practice. Outcomes: Bullying and incivility can be resolved in the workplace when competencies are set forth by nursing leaders to educate and empower nursing staff on expectations of healthy work environments. Conclusion: Healthy workplaces are achievable when nurse leaders, such as CNLs, educate and empower nurses to have the expectation of healthy work environments not only for themselves, but for all nurses. © 2020 Wiley Periodicals LLC
6 citations (Crossref) [2023-10-31] tex.author_keywords: bullying; clinical nurse leader; incivility; nurses; the hollow tex.coden: NUFOA tex.document_type: Article tex.pubmed_id: 33350483 tex.source: Scopus
Keywords: Bullying; Humans; Incivility; Nurses; Workplace; article; bullying; clinical nurse leader; dept.nur; expectation; human; incivility; leadership; nurse; nurses; nursing practice; nursing staff; peer-reviewed; reasoning; the hollow; theoretical study; work environment; workplace

Evaluation of an innovative curriculum enhancement: The conversation project - Pagano, Michael; Manger, Diana R.; O'Shea, Eileen; O'Sullivan, Cynthia (Nursing Education Perspectives, 2020)
Two northeast nursing schools piloted an innovative curriculum to teach The Conversation Project (TCP) to the next generation of nurses. The goal was to educate 26 graduate nursing students about how to have end-of-life and advance care planning conversations with people before they experience a crisis. The focus of assignments was on communicating newly learned TCP information. Postreflections demonstrated that participants felt their communication skills had been enhanced while their anxieties were reduced. The students' abilities to have end-of-life conversations increased. © Lippincott Williams & Wilkins.
0 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85094221077
Keywords: Advance Care Planning; Communication; Conversation Project; Curriculum; End-of-Life Care; Graduate Nursing Education; Humans; Learning; Schools; Nursing; Students; Nursing; adult; advance care planning; anxiety; article; clinical article; communication skill; conversation; curriculum; dept.nur; female; graduate nursing student; human; interpersonal communication; learning; male; nursing education; nursing student; peer-reviewed

Reducing Student Nurse Stigmatization of the Patient Who Misuses Opioids A Scoping Review - Maynard, Kristi (Journal of Addictions Nursing, 2020)
The United States is in the midst of an opioid epidemic. The numbers of opioid-related deaths have been steadily climbing, magnifying the need for innovative intervention. Stigma is a set of preconceived, negative assumptions about a patient population or group. Stigma is a known deterrent to communication and the delivery of healthcare. Nurses serve as a primary contact for many marginalized patients within the healthcare system. The purpose of this scoping review is to gather known data on the use of educational interventions with nursing students to reduce stigmatizing tendencies. Inclusion criteria constituted an educational intervention involving student nurses and an effort to reduce stigmatizing attitudes toward patients who misuse opioids. The intervention must have taken place in an institute of higher learning between the years of 2003 and 2018. Exclusion criteria included community-wide studies. A single study was identified addressing nursing student reduction of stigmatization of the individual who uses opioids, and so, the search was expanded to include any student nursing intervention developed to reduce stigma toward any marginalized population. The following electronic databases were utilized in the search process: Cumulative Index of Nursing and Allied Health Literature, Google Scholar, Journal Storage, Microsoft Academic, and ScienceDirect. Reference pages of selected or related articles were reviewed in an attempt to identify additional pertinent literature through citation mapping. Fifteen studies were identified, each of which utilized a variable methodology for stigma reduction with varying levels of success. © Lippincott Williams & Wilkins.
3 citations (Crossref) [2023-10-31] WOS:000526707500008
Keywords: Attitude of Health Personnel; Clinical Competence; Humans; Opioid-Related Disorders; Social Stigma; Stereotyping; Students; Nursing; clinical competence; dept.nur; education; health personnel attitude; human; nurse; nursing student; opiate addiction; opioid misuse; peer-reviewed; psychology; social stigma; stereotyping; stigma; student

Equity, achievement, and thriving in nursing academic progression - Aragon, Sofia; Beauvais, Audrey M.; Friday, Vivienne; Green, Cheryl; Kiger, Anna J.; King, Simmy; Lear, Tina; Mahowald, Jane; McGuill, Gail; Perkins, Danielle; Valdez, Anna Maria; Velasco, Brian; et al. (Teaching and Learning in Nursing, 2020)
8 citations (Crossref) [2023-10-31] tex.ids: aragonEquityAchievementThriving2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088786114 type: Article
Keywords: dept.nur; equity; nursing education; peer-reviewed; progression

Nurses and Patients' Perspectives on Spiritual Health Assessment - Green, Cheryl (Journal of Religion & Health, 2020)
Nurses conduct physical and psychosocial assessments during admissions to healthcare facilities. Patients rely upon nurses to provide support and education during their journey, from periods of health decline to states of optimal wellness. Therefore, nurses are an ideal population to assess spiritual health. The value and necessity of spiritual assessment were explored on an inpatient unit providing medical and palliative care to patients. Two spiritual assessment tools, comprised each of five items, were evaluated by nursing staff and patients. Spiritual Assessment Tool 1 used language that was unaffiliated with religion, nor a belief in God, and Spiritual Assessment Tool 2 used language affiliated with faith and belief in God. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
2 citations (Crossref) [2023-10-31] WOS:000584350300004
Keywords: Attitude of Health Personnel; Humans; Nursing Staff; Palliative Care; Patients; Religion; Spirituality; adult; article; dept.nur; health personnel attitude; hospital patient; human; language; nursing staff; palliative therapy; patient; peer-reviewed; religion

Editorial for special collection: Current issues and practices in school nursing - Resha, Cheryl (SAGE Open Nursing, 2020)
1 citations (Crossref) [2023-10-31] tex.ids: reshaEditorialSpecialCollection2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85082958509 type: Editorial
Keywords: dept.nur; peer-reviewed

Enough Is Enough: Confronting Workplace Bullying and Incivility - Green, Cheryl Ann (STTI, 2020)
tex.ids: greenEnoughEnoughConfronting2020
Keywords: dept.nur; ⛔ No DOI found

Challenging case in clinical practice: S-adenosyl methionine for mood support during corticosteroid therapy - Adimando, Andrea (Alternative and Complementary Therapies, 2020)
0 citations (Crossref) [2023-10-31] tex.ids: adimandoChallengingCaseClinical2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086454876 type: Article
Keywords: dept.nur

Narrative orphaned: When grief overwhelms - Green, Cheryl (Journal of Psychiatric and Mental Health Nursing, 2021)
What is known on the subject?: The loss of a parent for an adult can be devastating and can impact other relationships. The adult, in absence of parental love and support, may question their own identity. What this paper adds to existing knowledge?: A narrative is used to explain the adults’ experience of parental death and their new identity of being orphaned. What are the implications for practice?: Increased awareness for adults grieving the loss of a parent(s), as to the normalcy of feeling orphaned Adults grieving the death of a parent(s) are provided resources and support in addressing their grieving process. Abstract: Introduction When a parent dies during their child's adulthood, the life of the adult is altered as the familiarity of parental love and safety changes. The isolation and loneliness penetrates deeply as the orphaned adult must now navigate their world in absence of the most significant people in their lives, their parents. Aim To assist persons affected by parental death in understanding the normalcy of feeling orphaned while grieving. Method The use of a personal narrative to provide mental health support to others. Results The resumption of a routine that existed before parental death is possible, but takes time. Intermittent periods of grief can occur throughout one's life. Discussion When grief interrupts one's ability to function daily and the affected adult has relationships impacted by their parent's death, it is recommended that the adult seek mental health treatment. Implications for Practice Narratives can be used with persons affected by parental loss, to provide an example of normal versus complicated grieving and identify when mental health treatment is needed. © 2020 John Wiley & Sons Ltd
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85084478941
Keywords: Adaptation; Adult; Child; Emotions; Grief; Humans; Loneliness; Mental Health; Parents; Psychological; adult; child; child parent relation; coping behavior; dept.nur; emotion; grief; human; loneliness; mental health; peer-reviewed

Equity and diversity in nursing education - Green, Cheryl (Teaching and Learning in Nursing, 2020)
Retention and development of ethnically diverse nursing students may be more likely to occur when nursing faculty receive training on factors that can impact academic success. By understanding complex school system dynamics in low-income areas, cultural, linguistic, gender, age, religion, and ethnic differences, students’ strengths can be readily recognized, embraced, and encouraged by nursing faculty. When the necessity of equity and diversity is recognized within nursing education, this may potentially translate to retention and completion of nursing programs by nursing students from diverse backgrounds, thereby increasing diversity within the nursing profession. © 2020 Organization for Associate Degree Nursing
14 citations (Crossref) [2023-10-31] tex.ids: greenEquityDiversityNursing2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85089451312 type: Article
Keywords: Diversity; Equity; Nursing education; Nursing faculty; Nursing students; academic success; article; dept.nur; ethnic difference; female; gender; human; human experiment; lowest income group; male; nursing education; nursing student; occupation; peer-reviewed; religion

Should nursing be considered a STEM profession? - Green, Cheryl; John, Lori (Nursing Forum, 2020)
Background: The National Science and Technology Council developed a 5-year plan in 2013 to ensure that science, technology, engineering, and mathematics (STEM) experienced sustained growth within the United States (US). Nursing is comprised of multiple sciences that include chemistry, physics, biology, microbiology, anatomy and physiology, pharmacology, and the social and behavioral sciences of sociology, developmental lifespan psychology, and psychology. Science, technology, engineering, and math constitute the traditional STEM acronym. Nursing programs graduate nurses with both the rigorous academic coursework and diverse clinical skills necessary to provide patient care. These skills employed by nurses in the clinical setting can serve as the basis for the inclusion of the nursing profession as a STEM-designated profession by the federal government and educational institutions within the US. Problem: Currently, the US government does not acknowledge the profession of nursing as a STEM-designated profession. Acknowledgment of nursing as a STEM profession could potentially make more funding available for nursing education within the US and address nursing shortages both in clinical and academic settings. As well as position professional nurses for careers not only within the health sector but that of business and industry because of nurses’ STEM knowledge. Hence, enhancing the growth of STEM within the US and creating global market economic competitiveness with new innovation development. Approach: In the practice of nursing, nurses apply the sciences, math, and innovative technology in the assessments, diagnoses, and planning of patients’ care. Nurses implement scientifically-based interventions to treat illness and sustain human life and to ultimately evaluate the outcomes of the care provided to patients. Outcomes: Methodologies of evaluation of outcomes of patient care status post nursing interventions (ie, administration of intravenous antibiotics to treat pneumonia) are based upon rationales that have been derived from evidenced-based practice and nursing research; both originating from applied STEM knowledge. Conclusion: The formal designation by the US federal government, for nursing to be recognized as a STEM profession, can increase funding to the nursing profession and enhance the diversity of employment opportunities for nurses in industry and business. Thereby potentially decreasing nursing shortages and bringing national and worldwide recognition to nursing in both academia, industry, business, and clinical settings, as a profession contributing to the science of improvement of the health of all people through STEM knowledge. © 2019 The Authors. Nursing Forum published by Wiley Periodicals, Inc.
5 citations (Crossref) [2023-10-31] tex.ids: greenShouldNursingBe2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85076273828 type: Article
Keywords: Humans; Professional Role; STEAM; STEM; Science; classification; dept.nur; education; health care; human; inclusion; innovation; nursing; professional standard; science

Tick-borne illness - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Tracheostomy care - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Trauma informed care - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Varicella - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Uncertainty in transitions of African American caregivers - Unson, Christine; Flynn, Deborah; Chukwurah, Queendalene; Glendon, Maryann; Testut, Tammy (Issues in Mental Health Nursing, 2020)
The purpose of this study was to gain an understanding of the ambiguities and uncertainties experienced by a diverse group of African-American caregivers. The study applied Schlossberg's transition theory (TT) and Mishel’s revised uncertainty theory to narratives of self-identified African-American caregivers who provided care at least 5 h a week. The men (6) and women (8) were mostly unmarried, mostly caring for a parent or grandparent. The caregivers’ average age was 52 (SD = 19; ages ranged from 24 to 82 years); and the care recipients’ average age was 84 (SD = 9). Six care recipients had dementia and the remainder had multiple disease diagnoses. Narratives were obtained by in-depth interviews or focus group discussions. These were audio-recorded, transcribed verbatim professionally and analyzed independently by trained coders. Schlossberg’s TT contextualized whereas Mishel’s RUIT illuminated the characteristics of the transition, its associated uncertainty, and their relationship to the development of caregiver stress. Situational factors such as difficulties with illness symptoms of the care recipient, conflict between previous experience and current expectations and the adjustments to the new caregiving role, burdened younger caregivers more than older caregivers. Self-factors related to lack of knowledge about the illness and feelings of lack of control. Social support was predominantly provided by family members, and its absence resulted in conflict among siblings and caregiver stress. The most common coping strategies include religiosity, expectations of reciprocity, and coming to terms with the uncertainty. Understanding the feelings, perceptions and needs of caregivers in transition is tantamount to providing nursing care.
4 citations (Crossref) [2023-10-31]
Keywords: Adaptation; Psychological; Adult; African American; African Americans; Aged; Aged; 80 and over; Caregivers; Female; Grandparents; Humans; Male; Middle Aged; Narration; Parents; Social Support; Stress; Psychological; Uncertainty; Young Adult; adult; aged; caregiver; child parent relation; coping behavior; dept.nur; dept.pch; female; grandparent; human; male; mental stress; middle aged; peer-reviewed; psychology; social support; uncertainty; verbal communication; very elderly; young adult

Using Kolb’s Experiential Learning to Educate Nursing Students About Providing Culturally and Linguistically Appropriate Care - Krol, Maria; Adimando, Andrea (Nursing Education Perspectives, 2021)
Over the past decade, the Agency for Healthcare Research and Quality and The Joint Commission have identified that communication problems are a root cause of most serious adverse events and that patients with limited English proficiency are more likely than others to suffer physical harm when such errors occur. It is essential to educate nursing students on the challenges of patients with limited English proficiency and empower them with tools, such as the National Culturally and Linguistically Appropriate Services standards, to minimize this phenomenon in their future nursing practice. We describe an educational intervention designed to accomplish this using Kolb’s experiential learning theory as a foundation for implementation.
0 citations (Crossref) [2023-10-31]
Keywords: Humans; Nursing; Problem-Based Learning; Students; article; dept.nur; experiential learning; human; limited English proficiency; nursing student; peer-reviewed; problem based learning; transcultural care

Autistic spectrum disorders - Adimando, Andrea (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITIONEVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Mental health - Adimando, Andrea (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITIONEVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Suicide - Adimando, Andrea (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITIONEVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

School nurse guidelines for: Abrasions - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Allergies - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Bipolar disorders - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Cardiac conditions - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Depression - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Developmental disabilities - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Enuresis - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Fractures - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Human Papillomavirus (HPV) - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Mosquito-borne disease - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Puncture wounds - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: skin and soft tissue infection (Boils, Cellulitis, Lymphangitis, and MRSA) - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

Teaching accelerated nursing students’ self‐care: A pilot project - Green, Cheryl (Nursing Open, 2020)
Aim A benchmark of 4 has been determined for the reduction of self-reported stress by nursing students’ status post 5 weeks of holistic educational activities and interventions provided by a nurse educator. Design Provision 5 in the American Nurses Association Code of Ethics for Nurses with Interpretive Statements emphasizes the duty of the nurse to not only promote the health and safety of others, but to self as well (ANA, 2015, Code of ethics with interpretive statements, Nursebooks.org). A self-care for nurses’ pilot project was trialled with 25 accelerated nursing students over the course of 5 weeks. Holistic education programmes were facilitated by a nurse educator uninvolved in providing clinical or classroom education to the students. Methods The Standards for Quality Improvement Reporting Excellence (SQUIRE) guidelines are used in this pilot project as a framework to explore standardization of education of nursing students about self-care in nursing programmes and to promote positive health behaviours and student nurses’ insight into how nurses’ self-care can have an impact on patient outcomes. The self-care pilot project introduced the importance of self-care for the pre-licensure nursing student by teaching healthy eating, physical exercise, the value of sleep, use of positive affirmations and aromatherapy to a cohort of accelerated nursing students over the course of 5 weeks. The Star Model of Knowledge Transformation was the theoretical framework for the pilot study. Two questionnaires were used by the principal investigator to obtain participant data, the Project Participant Questionnaire and the Final-Year Group Questionnaire. Results On completion of the self-care for nurses’ pilot, the nursing students reported a reduction in stress and an increased ability to cope with stress after exposure to different holistic stress reduction strategies. An average benchmark of 4.36 was achieved indicating that the nursing students’ self-care had improved status post the interactive teaching intervention. Self-care taught to pre-licensure nursing students by nurse educators can enhance their self-awareness of the importance of stress reduction and care of themselves while enduring the academic rigour and simultaneous clinical practicum experiences in nursing programmes. Applying self-care behaviours to reduction of stress for nursing students may be of benefit to of students as they transition from the pre-licensure to graduate nurse roles. Hence, teaching health behaviours that are self-protective and contribute to maintaining safe clinical environments for nurses and the patients in their care.
10 citations (Crossref) [2023-10-31] tex.ids: greenTeachingAcceleratedNursing2019, lens.org/169-203-251-554-761
Keywords: dept.nur; nurse educators; nursing students; peer-reviewed; self-care; stress reduction